2009
DOI: 10.1038/cr.2009.67
|View full text |Cite
|
Sign up to set email alerts
|

Ten1p promotes the telomeric DNA-binding activity of Cdc13p: implication for its function in telomere length regulation

Abstract: In Saccharomyces cerevisiae, the essential gene CDC13 encodes a telomeric single-stranded DNA-binding protein that interacts with Stn1p and Ten1p genetically and physically, and is required for telomere end protection and telomere length control. The molecular mechanism by which Ten1 participates in telomere length regulation and chromosome end protection remains elusive. In this work, we observed a weak interaction of Cdc13p and Ten1p in a gelfiltration analysis using purified recombinant Cdc13p and Ten1p. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
(76 reference statements)
4
21
0
1
Order By: Relevance
“…Consistent with the increased Cdc13 telomere binding observed in ykuD strains (Fisher et al 2004) and in late S/G2 when telomeres transiently have longer single-stranded termini (Taggart et al 2002), an increase in the single-stranded nature of the elongated ten1-ts telomeres would be expected to promote the overall extent of Cdc13 association in these strains. These data are consistent with the interpretation that Ten1 is not necessary for Cdc13 to bind telomeres in vivo, in agreement with Qian et al (2009).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with the increased Cdc13 telomere binding observed in ykuD strains (Fisher et al 2004) and in late S/G2 when telomeres transiently have longer single-stranded termini (Taggart et al 2002), an increase in the single-stranded nature of the elongated ten1-ts telomeres would be expected to promote the overall extent of Cdc13 association in these strains. These data are consistent with the interpretation that Ten1 is not necessary for Cdc13 to bind telomeres in vivo, in agreement with Qian et al (2009).…”
Section: Resultssupporting
confidence: 82%
“…Wild-type Ten1 protein expression is not as robust; it is not clear if this is a factor in the apparently weaker two-hybrid interactions of wild-type Ten1 at 23°( Figure 1D). The Ten1-103 protein reproducibly shows altered mobility on SDS-PAGE; it was recently shown that mutating the adjacent residue (R47E) also impacts Ten1 gel migration (Qian et al 2009). Next, Ten1 interaction was tested with Stn1 and Cdc13 across a range of temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Stn1 contains binding domains for both Cdc13 and Ten1, which are essential for the formation of the heterotrimeric Cdc13-Stn1-Ten1 (CST) complex at the chromosome ends. In the absence of Stn1, the interaction between Cdc13 and Ten1 is unstable (22). Recent bioinformatic analysis and protein structure modeling have indicated that Stn1 and Ten1 share several structural similarities with Rpa2 and Rpa3, the subunits of the replication protein A (RPA) complex (5,23,24).…”
mentioning
confidence: 99%